LGBT Movement: Existence and Responsiveness of Marriage Law In Indonesia - Yusril Bariki; Fitriana Nur Rohmah; Ali Muhtarom (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
This research examines the LGBT movement which is at odds with the issue of marriage law in Indonesia. With a library research approach, this research collects data and information through journal literature, news, and books. The research results show that the existence of lesbians or the like is contrary to the values of Pancasila. The responsiveness of marriage law to the LGBT movement is very firm in rejecting it, whereas, in Law No. 1 of 1974 concerning Marriage, marriage is only permitted for men and women. In the view of the Al-Qur'an and Hadith, the existence of LGBT harms the nature that Allah has given. Because the legal aim of marriage is to form a happy, eternal family and a means of channeling biological desires. So the existence of the LGBT movement destroys the values that have been built into marriage law.